Attracting Shoppers To Shopping Malls: The Malaysian Perspective - Kamarulzaman, Y.; Lih, F.L.C. (Cabells USA, 2010)
Competition among shopping malls has led retailers to consider key factors of motivating patrons to shop at their malls and stay longer. The purpose of this study is to assess the factors that influence Malaysians to visit shopping malls. A survey was conducted to assess mall-directed shopping habits and patrons shopping motivation. A total of 317 respondents took part in the survey in the shopping malls located in Kuala Lumpur, the capital city of Malaysia. A structured questionnaire was used as the main instrument in this survey. The results show that Malaysian shoppers are motivated to visit malls because of the ambience, interior design of the malls, convenience, accessibility and promotion. Evidence shows that there is a strong relationship between shopping mall characteristics and actual action of shoppers in visiting shopping malls. In summary, the results of the study have several implications that will be beneficial for retail industry, especially shopping mall retailers.